Multiple Masculinities and the Schooling of Boys - Imms, Wesley (Canadian Journal of Education/Revue canadienne de l’éducation, 2000)
Many disciplines have discussed masculinity in often quite polarized discourses. Resulting theories and accounts fail to describe adequately its complex structure. One consequence is the lack of a suitable platform for studying masculinity in schools. Recent discussion of “multiple masculinities” bridges these discourses to present a pluralist interpretation of how boys and men construct and enact their masculinities. It provides an analytical tool for examining how masculinities are built in school and offers educators a three-level strategy for working with boys. La masculinité fait l’objet de discours souvent très polarisés dans bien des disci- plines. Les théories et les explications qui en résultent ne décrivent pas adéquate- ment sa structure complexe. L’une des conséquences est l’absence d’une plateforme convenable pour l’étude de la masculinité dans les écoles. L’examen récent de la question des « multiples masculinités » fait le lien entre ces discours afin de pré- senter une interprétation pluraliste de la manière dont les garçons et les hommes se forgent et vivent leurs masculinités. Il fournit un outil analytique pour étudier comment les masculinités se construisent à l’école et propose aux éducateurs une stratégie tripartite dans leur travail auprès des garçons.